Analysis of The Constructivist Approach in The Learning Process of Public Policy - Putri, Adinda Sakina; Radandima, Grandy Umbu Endalu; Setiawan, Arvan (Jejaring Administrasi Publik, 2024)
The constructivist approach to education emphasizes the active participation of students in knowledge-building through direct experiences, social interactions, and later reflection. This article analyses constructivism as a philosophical framework within public policy education, promoting the evolution of conventional learning into a more dynamic, participatory, and adaptive process. This method transforms educators from information providers to facilitators who create learning environments promoting inquiry and cooperation. Rather than only measuring the quantity of retained knowledge, constructivism prioritizes evaluation as a pedagogical approach that emphasizes the cultivation of a deep understanding of concepts and their application in real-world contexts. In conclusion, the constructivist technique fosters a learning environment that is both pertinent and inclusive, promoting the growth of students into critical, creative, and independent individuals. Incorporating constructivism into the curriculum could enhance the efficacy of public policy education in equipping students to address the challenges and intricacies of contemporary society. Keywords: Constructivism, Education, Social Interaction, Public Policy